Synthesis and cytotoxicity of oxindoles dispiro derivatives with thiohydantoin and adamantane fragments. (2nd July 2020) - Kukushkin, Maxim E.; Skvortsov, Dmitriy A.; Kalinina, Marina A.; Tafeenko, Viktor A.; Burmistrov, Vladimir V.; Butov, Gennady M.; Zyk, Nikolai V.; Majouga, Alexander G.; Beloglazkina, Elena K.
Abstract: An effective and highly regio- and diastereoselective one-pot synthesis of two types of dispiro heterocyclic systems (2-thioxodispiro[imidazolidine-4, 3′-pyrrolidine-2′, 3″-indoline]-2″, 5-diones and 2-thioxodispiro[imidazolidine-4, 3′-pyrrolidine-4′, 3″-indoline]-2″, 5-diones) comprising pyrrolidinyl-oxindole, thiohydantoin and adamantane moieties has been developed based on a 1, 3-dipolar cycloaddition of azomethine ylides, generated from isatin and sarcosine or formaldehyde and sarcosine, to adamantane-containing electron-deficient alkenes. Several molecules have demonstrated a considerable cytotoxicity against A549, HEK293T, MCF7 and VA13 cancer cell lines. The possible mechanism of anticancer activity of the synthesized compounds based on literature data may be the inhibition of p53/MDM2 interaction; however, we did not observe significant p53 activation using a reporter construction in A549 cell line in the relevant concentration range. Graphical Abstract: uf0001